2020
DOI: 10.3389/fchem.2020.00258
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of Synthetic Trisaccharide of Staphylococcus aureus Type 8 Capsular Polysaccharide Elicits Antibodies Recognizing Intact Bacterium

Abstract: Staphylococcus aureus causes a wide range of life-threatening diseases. One of the powerful approaches for prevention and treatment is to develop an efficient vaccine as antibiotic resistance greatly increases. S. aureus type 8 capsular polysaccharide (CP8) has shown great potential in vaccine development. An understanding of the immunogenicity of CP8 trisaccharide repeating unit is valuable for epitope-focused vaccine design and cost-efficient vaccine production. We report the chemical synthesis of conjugatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The results showed a strong immune response to the chemical synthesis of conjugation-ready CP8 trisaccharide 1 in mice, demonstrating that synthetic trisaccharide 1 could be an effective antigen for vaccine development. The results of Zhao et al [9] give a new horizon for researchers to continue the development of approved CP vaccines, particularly in light of the results of our current study in Jordan, where we discovered that most of the clinical isolates are capsule genotypes (91.3%) with a predominance of CP8 (88.6%). These findings provide hope for the development of a more effective vaccine for mastitis.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…The results showed a strong immune response to the chemical synthesis of conjugation-ready CP8 trisaccharide 1 in mice, demonstrating that synthetic trisaccharide 1 could be an effective antigen for vaccine development. The results of Zhao et al [9] give a new horizon for researchers to continue the development of approved CP vaccines, particularly in light of the results of our current study in Jordan, where we discovered that most of the clinical isolates are capsule genotypes (91.3%) with a predominance of CP8 (88.6%). These findings provide hope for the development of a more effective vaccine for mastitis.…”
Section: Discussionmentioning
confidence: 54%
“…Vaccines based on bacterial polysaccharides protect against many dangerous pathogens and save millions of lives annually [30]. Several trials have been undertaken to develop S. aureus CP5-and CP8-based vaccines, and a recent study by Zhao et al [9] showed the great potential of S. aureus CP8 in vaccine development. The results showed a strong immune response to the chemical synthesis of conjugation-ready CP8 trisaccharide 1 in mice, demonstrating that synthetic trisaccharide 1 could be an effective antigen for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[127][128] This glucosylation-epimerization-oxidation approach continue finding broad applications in synthesis. Among effective recent applications are the syntheses of trisaccharide derived from membrane protein integrase (MPIase), [129][130] trisaccharide repeating unit of enterobacterial common antigen (ECA), [131] various oligosaccharides derived from Staphylococcus aureus CP5 [132][133] and CP8, [134][135][136] and Streptococcus pneumonia serotype 12A and 12F. [137] Illustrated herein is a recent example from the Demchenko group that involves the synthesis of a hexasaccharide representing two repeat units of S. aureus CP8.…”
Section: Mannosaminuronic Acid (Mannaca) Glycosidesmentioning
confidence: 99%